REINGENIERÍA DE PROCESOS EN EL ÁREA DE RECURSOS HUMANOS DE LA EMPRESA CONSORCIO CONTACOM S.A.C. PARA MEJORAR EL ÍNDICE DE DESEMPEÑO DEL PERSONAL - Chambergo Colona, Samantha Ingrid (2007)
This study focused on the company Contacom Consortium S.A.C. dedicated to providing consulting services, the problems presented this entity is the lack of standardization of its human resources processes and inefficiency in implementation thereof, which is affecting its operation, through the investigation has identified the shortcomings outlined in the problem. Responding effectively to the formulation and systematization of the respective hypothesis problem was raised. The methodological framework is composed of the types of research that applied to support the proposal, where the universe to calculate the sample was determined using the research tool known as the survey, ie the collection, tabulation and analysis of the instrument research where it was found that the company has empirical flowcharts, why operational efforts are not met on time, so has generated an unsatisfactory level customers. Why reengineering process proposed in the area of Human Resources of the company Consorcio Contacom S.A.C. where different processes are observed. Finally the respective conclusions and recommendations help managers of this work leave a precedent to the problems that arose and its solution, which is at the discretion of senior management of the management company under study or established those companies that have the same problem.